2020
DOI: 10.1155/2020/4381346
|View full text |Cite
|
Sign up to set email alerts
|

Miscarriage on Endometriosis and Adenomyosis in Women by Assisted Reproductive Technology or with Spontaneous Conception: A Systematic Review and Meta-Analysis

Abstract: Background. In the past several years, there has been an increasing concern on miscarriage caused by endometriosis or adenomyosis. However, the results reported by different studies remain controversial. The present study is aimed at assessing the impact of endometriosis and adenomyosis on miscarriage. Materials and Methods. Searches were carried out in PubMed, Embase, and the Cochrane library for studies published from inception until February 29, 2020. The investigators included studies that evaluated miscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 68 publications
(13 reference statements)
0
28
0
1
Order By: Relevance
“…Third, many researchers believed that patients with adenomyosis have significantly lower pregnancy and implantation rates, 36,37 and higher miscarriage rates, 38 adversely affect IVF results, increase the risk of obstetric complications such as preterm birth and premature rupture of membrane, compared to women without adenomyosis. 4,11,38 Women with infertility may have undergone surgical treatment at a young age due to frequent visits to medical institutions. Due to the small number of infertility patients and the very high odds ratios of age, parity, and DIE, no significant association was found between the adenomyosis phenotype and infertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, many researchers believed that patients with adenomyosis have significantly lower pregnancy and implantation rates, 36,37 and higher miscarriage rates, 38 adversely affect IVF results, increase the risk of obstetric complications such as preterm birth and premature rupture of membrane, compared to women without adenomyosis. 4,11,38 Women with infertility may have undergone surgical treatment at a young age due to frequent visits to medical institutions. Due to the small number of infertility patients and the very high odds ratios of age, parity, and DIE, no significant association was found between the adenomyosis phenotype and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Third, many researchers believed that patients with adenomyosis have significantly lower pregnancy and implantation rates, 36 , 37 and higher miscarriage rates, 38 adversely affect IVF results, increase the risk of obstetric complications such as preterm birth and premature rupture of membrane, compared to women without adenomyosis. 4 , 11 , 38 However, it is not clear which phenotype of adenomyosis causes infertility. Univariate analysis revealed that infertile women were younger, had lower gravity and parity, and more frequent coexistence of OMA and DIE/SUP compared with fertile women.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Comparison of baseline data between two groups GROUP A(n=160) [1] GROUP B(n=181) [4] 0.91 0.18 0.02 [1] the study group (n = 160) was added GnRH-a based on GnRH-a before using hormone to adjust menstruation period. [2] The control group (n = 181) was only treated by artificial hormone cycle to prepare emdometrium.…”
Section: Tablesmentioning
confidence: 99%
“…[3] One value was missing. [4] Five values were missing. [1] the study group (n = 160) was added GnRH-a based on GnRH-a before using hormone to adjust menstruation period.…”
Section: Tablesmentioning
confidence: 99%
See 1 more Smart Citation